Synthesis, spectroscopic characterization and biological applications of Cu(II) and Ni(II) complexes with 2-butyl-4-chloro-5-formylimidazole thiosemicarbazone - A. Sreenath Reddya, L. Sivarama Krishnaa, H. K. Rashmib, P. Uma Maheswari Devib, Y. Saralac, A. Varada Reddya (Journal of Applied Pharmaceutical Science, 2016)
Cu(II) and Ni(II) complexes of 2-butyl-4-chloro-5-formylimidazole thiosemicarbazone (L) are synthesized and characterized by using spectroscopic techniques like elemental analysis, FT-IR, mass spectrometry, electronic and EPR spectra. The complexes are found to have characteristic electronic spectra and the geometry of the complexes are identified as octahedron. Both the complexes are found to exhibit similar anti-microbial activity against the gram –ve and gram +ve bacteria. Anti-cancer activity against the cancer cell lines (MDA-MB 231 cell lines) among the compounds studied for % of viability, the inhibition concentration 50 values were shown by Cu(II)-L complex at 80 mg/ml and by Ni(II)-L complex at 100 mg/ml.
Keywords: Cu(II) and Ni(II) complexes, EPR spectra, antimicrobial activity, MDA-MB 231 cell lines.